2007
DOI: 10.1073/pnas.0701806104
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of nucleophosmin/B23 regulates its subcellular localization, mediating cell proliferation and survival

Abstract: Nucleophosmin/B23 is a major multifunctional nucleolar phosphoprotein that plays a critical role in ribosome biogenesis and cell proliferation. Arf tumor suppressor binds B23 and enhances its sumoylation. However, the biological effects of this event remain unknown. Here we show that B23 is sumoylated on both Lysine 230 and 263 residues, but the latter is the major one. Mutation of K263, but not K230, into R abolishes its centrosomal and nucleolar residency. Moreover, Rb binds to wild-type B23, but fails to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 31 publications
7
89
0
Order By: Relevance
“…It is involved in a complex network of interactions and has multiple functions involved in the ribosomal biosynthesis (Herrera et al, 1995;Savkur et al, 1998), control of centrosome reproduction (Okuda, 2002), cell apoptosis (Liu et al, 1998), molecular chaperones (Okuwaki et al, 2001), environmental stress responses (Kurki et al, 2004), the regulation of the tumor suppressor proteins p53 (Colombo et al, 2002) and p14ARF (Bertwistle et al, 2004), and post-translational modification by acetylation (Swaminathan et al, 2005), sumoylation (Liu et al, 2007), ubiquitinylation (Sato et al, 2004), and phosphorylation (Okuda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in a complex network of interactions and has multiple functions involved in the ribosomal biosynthesis (Herrera et al, 1995;Savkur et al, 1998), control of centrosome reproduction (Okuda, 2002), cell apoptosis (Liu et al, 1998), molecular chaperones (Okuwaki et al, 2001), environmental stress responses (Kurki et al, 2004), the regulation of the tumor suppressor proteins p53 (Colombo et al, 2002) and p14ARF (Bertwistle et al, 2004), and post-translational modification by acetylation (Swaminathan et al, 2005), sumoylation (Liu et al, 2007), ubiquitinylation (Sato et al, 2004), and phosphorylation (Okuda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…NPM1 undergoes rapid and reversible translocation from the nucleolus to the nucleoplasm (nucleoplasmic translocation) upon exposure to UV irradiation, oxidative stress, heat shock or numerous DNA-damaging agents including mitomycin C, methyl methanesulfonate (MMS) and cisplatin; however, NPM1 does not alter its localization in response to ionizing radiation (IR) or exposure to double strand break (DSB)-inducing topoisomerase inhibitors such as etoposide or camptothecin (Kurki et al 2004;Vanderwaal et al 2009;Yogev et al 2008). Importantly, these localization changes do not coincide with relocalization of NCL or a generalized dissociation of the nucleolus as seen in response to RNA Pol I inhibition, and evidence is emerging for their control by particular, DNA-damage-responsive signaling pathways and/or post-translational modifications (Kurki et al 2004;Liu et al 2007;Sato et al 2004;Vanderwaal et al 2009;Yogev et al 2008). Given such evidence, it is likely that the nucleoplasmic translocation of NPM1 is an active and controlled response to particular genotoxic stress conditions and not the result of generalized nucleolar disruption.…”
Section: Nucleophosmin and Nucleolin: Two Multifunctional Nucleolar Pmentioning
confidence: 99%
“…Separate groups have also used a biochemical assay for repair of a UV-irradiated reporter plasmid to demonstrate decreased NER activity following either overexpression of NCL (Yang et al 2009) or depletion of NPM1 (Wu et al 2002b), suggesting that these proteins may have opposing activities in NER regulation. It is important to note, however, that neither of these experimental approaches are able to differentiate between direct activities of NPM1/NCL at sites of NER and global NER deficiencies arising indirectly, such as from NPM1/NCL-dependent transcriptional modulation of the NER machinery (Lin et al 2010;Liu et al 2007;Wu et al 2002a;Wu et al 2002b). Indeed, Wu et al (2002aWu et al ( , 2002b observed that expression levels of PCNA were closely correlated with those of NPM1 in their system, likely explaining the observed effects on NER efficiency.…”
Section: Fix It or Fudge It: Alternative Responses To Uv-induced Damamentioning
confidence: 99%
“…8,9 NPM also regulates the tumor suppressor proteins p53 10 -12 and p14 ARF . [13][14][15] Moreover, NPM protein is post-translationally modified by acetylation, 16 sumoylation, 17,18 ubiquitinylation, 19 and phosphorylation. 20 -23 NPM has been heavily implicated in cancer pathogenesis, but its actual role in oncogenesis is controversial.…”
mentioning
confidence: 99%